Primary Corneal Hemangiosarcoma in a Tapir (Tapirus terrestris) - Torrecilhas Jorge, Adriana; Teodoro de Oliveira, Laura; Teixeira Gomes Soares, Roberta; Modé Magalhães, Geórgia; Gomes Rocha, Thais; dos Santos Honsho, Cristiane (Acta Scientiae Veterinariae, 2022)
Background: Hemangiosarcoma is a malignant vascular tumor commonly described in veterinary ophthalmology as emerging at the margin of the third eyelid and bulbar conjunctiva. The primary corneal attachment of the tumor is considered rare, as the cornea is an avascular structure, but there are sparse reports of primary occurrences in the cornea of dogs, cats, and horses. No reports were found in wild animals. The Tapirus terrestris, commonly known as Tapir, is a perissodactyl mammal that inhabits South America regions, being considered the largest terrestrial mammal of Brazil and one of the most popular animals in zoos in various countries. This paper aims to report the first case of primary corneal hemangiosarcoma in a 25-year-old female Tapir (Tapirus terrestris) held in captivity. Case: A 25-year-old Tapirus terrestris female presented an irregular mass in the right cornea, mucopurulent secretion, and inconclusive previous cytological evaluation. It also had a history of a milky cornea for many years, and in the last 12 months, a tissue growth was observed, as well as the occurrence of mucopurulent secretion. The menace response in the right eye was negative. In the ophthalmologic examination, a red-colored, lobed, hemorrhagic, and ulcerated mass occupying approximately 90% of the cornea was observed, and in the peripheral cornea, there was an intense discoloration. Due to the extension of the mass and visual loss, the transpalpebral enucleation was performed under general inhalation anesthesia. The histopathological analysis evidenced a vascular tumor restricted to the central peripheral cornea, composed of blood vessels of small and large caliber, showing polygonal endothelial cells with moderate atypia, anisocytosis, and anisocariasis, in addition to dense stroma and inflammatory cells. The mass occupied the anterior corneal stroma, and there was no involvement of bulbar conjunctiva, sclera, or intraocular structures. The immunohistochemical study revealed the positivity of neoplastic cells for CD31, and the proliferative index of the lesion was evaluated by the Ki-67 as inferior to 10%. Discussion: The histopathologic and immunohistochemical examinations evidenced a hypercellular lesion, and the diagnosis of primary corneal hemangiosarcoma (HSA) was possible due to the significant cellular atypia identified in the lesion. To the authors’ knowledge, this is the first case of corneal hemangiosarcoma described in Tapir terrestris. The HAS is a malignant neoplasm originating in the vascular endothelial cells. There is a significant correlation between the HSA and prolonged exposure to solar radiation. The tapir of this report lived in a high-altitude region with exposure to ultraviolet rays; therefore, it might be an important predisposing factor for the HSA emergence. The chosen treatment for vascular tumors according to the visual prognostic is the lamellar keratectomy; however, the transpalpebral enucleation was the elected treatment since the eye was not visual, the neoplasm had a great extension, the animal was in advanced age and lived in captivity, and it was difficult to handle the animal without sedation to perform adjuvant therapies. Since the mass corresponded to 90% of the cornea, total removal with free edges would not be possible as described in the literature, and, therefore, there was an increased risk of relapse. In the follow-up after 3 years of surgical excision, the animal remained free of metastasis, reinforcing the diagnosis of primary corneal hemangiosarcoma. Keywords: immunohistochemistry, vascular tumors, histopathology, veterinary ophthalmology.